Comparison of Enterprises Extracting Building Materials in the Czech Republic - VANĚK, Michal; ČERNÝ, Igor; PITŘÍK, Jakub; KUBICA, Tomáš (GeoScience Engineering, 2020)
The article deals with the comparison of mining companies extracting building materials in the Czech Republic. First, the legal form of all companies operating in the selected raw material segment is analysed. Subsequently, the actual comparison of the enterprises is carried out, which includes the most important enterprises of the different raw material groups (brick raw material, dimension stone, building stone, gravel, and sand). Selected companies are compared in the period 2011-2018 using six indicators: ROA, inventory turnover, total debt, immediate liquidity, DHM productivity, net working capital turnover time. The weighted sum method is used for self-evaluation. Indicator weights are determined using the Fuller triangle. The comparison shows that the following companies are the best in the raw material groups: (i) Heluz s.r.o. (Ltd.) (brick clays), (ii) Granit Lipnice s.r.o. (Ltd.) (dimension stone), (iii) EUROVIA Kamenolomy, a.s. (Plc.) (building stone), (iv) Českomoravský štěrk, a.s. (Plc.) (gravel and sand). When comparing the companies in the whole building material segment, EUROVIA Kamenolomy, a.s. (Plc.) is the best company, followed by Kamenolomy ČR, s. r. o. (Ltd.) and KÁMEN Zbraslav (Plc.). The analysis also found that 54.24% of mining companies in the Czech Republic use the legal form of s.r.o. (Ltd.) and 26.69% are public or private limited companies – a.s. (Plc.). It was also found that the mining company with the highest production volume was not in first place in the group based on the comparisons made. Keywords: Building materials; Comparison; Mining company; Ratio indicators. DOI 10.35180/gse-2020-0034